2005
DOI: 10.1002/eet.384
|View full text |Cite
|
Sign up to set email alerts
|

Climate policy, ecological modernization and the UK emission trading scheme

Abstract: Since the election of the Labour government in 1997, leading to a flurry of policy documents utilizing ecological modernization language, the UK has seen a steady growth in the use of new environmental policy instruments, with the British government having launched in 2002 the world's first national economy-wide emission trading scheme for greenhouse gases. Among other things, the UK Emissions Trading Scheme aims at stimulating a transition of the UK towards a low-carbon economy. Reporting findings of a recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Second, it analyses if membership of the UK ETS is associated with differences in the disclosure of organisations that participate in it. As such, this analysis contributes not only to the literature on corporate disclosure but it also helps to understand how disclosures may change over time under the influence of the UK ETS (see also Nye & Owens, 2008;Roeser & Jackson, 2005;Von Malmborg & Strachan, 2005). The findings of this research report on a very specific policy instrument in the UK context so generalisations are difficult to infer.…”
Section: Final Commentsmentioning
confidence: 88%
See 1 more Smart Citation
“…Second, it analyses if membership of the UK ETS is associated with differences in the disclosure of organisations that participate in it. As such, this analysis contributes not only to the literature on corporate disclosure but it also helps to understand how disclosures may change over time under the influence of the UK ETS (see also Nye & Owens, 2008;Roeser & Jackson, 2005;Von Malmborg & Strachan, 2005). The findings of this research report on a very specific policy instrument in the UK context so generalisations are difficult to infer.…”
Section: Final Commentsmentioning
confidence: 88%
“…The UK Government seemed to have attracted direct participants with the idea that it would be cost-efficient to participate in the UK ETS. Indeed, von Malmborg and Strachan (2005) note that the main reason given by direct participants to engage in the UK ETS was to receive incentive payments. In the same vein, Nye and Owens (2008) suggested that organisations' primarily motivation in supporting economic instruments, such as emissions trading, is to achieve economic efficiency.…”
Section: Insights From New Institutional Sociologymentioning
confidence: 99%
“…Despite talk of extension in an altered form (see DEFRA, 2006), the passing of the original scheme attracted little political or media attention, nor was it publicly mourned by any of its participants. It is probably safe to conclude that the UK ETS will not be remembered as a fi nancial or legislative success (see Von Malmborg and Strachan, 2005;Roeser and Jackson, 2003;Sorrell, 2003;NAO, 2004;ENDS, 2002, among others). Ultimately, the analysis presented here suggests that the longer-term regulatory interests of a small number of powerful companies dominated the policy agenda surrounding UK emission trading, pushing through a relatively weak and complicated programme that had little to offer mainstream business.…”
Section: Lessons and Implicationsmentioning
confidence: 97%
“…ENDS, 2002;NAO, 2004), though the mechanisms and motives for participation are more complicated due to the offer of a fi nancial incentive and the absence of any mandatory arm of the programme. Important groundwork on business motives for participation in the UK ETS has been undertaken by a variety of researchers and organizations (see among others Von Malmborg and Strachan, 2005;Roeser andJackson, 2003, NAO, 2004;NERA, 2003;Enviros, 2003Enviros, , 2006DEFRA, 2002). In general, these studies identify three primary motives for participation, including a desire to take up the fi nancial incentive offered for participation in the UK ETS (in some cases as a method of subsidizing investment in effi ciency measures, or to offset Climate Change Levy payments), early mover considerations associated with gaining experience in emission trading prior to the introduction of the EU emission trading scheme and a desire to demonstrate environmental initiative to government and the public.…”
Section: Focus On Voluntary Emission Tradingmentioning
confidence: 99%
“…Von Malmborg and Strachan (2005) highlight the failings of the UK greenhouse gas emission trading scheme. According to their analysis, a central problem is that the scheme's design and implementation does not live up to the principles of EMT itself.…”
mentioning
confidence: 98%